More Than Just Peloteros : Sport and U.S. Latino Communities - Iber, Jorge, 1961- (Book collections on Project MUSE., 2014)
""Examines the history of Latino/a athletes in American sports, including baseball, boxing, football, basketball, and horse racing. Also evaluates the role of sports in Spanish-speaking culture in the US."